Analisis Komposisi Soundtrack Epic â€œYou See Big Girlâ€ Karya Hiroyuki Sawano dalam Serial Animasi Attack on Titan - Muliani, Metta (Universitas Negeri Surabaya, 2020)
Action-fantasy are some movie genres that has the most expansive franchises in film industry and tend to use cinematic music to correlate the atmosphere and emotions of the movieâ€™s imaginary universe. The analysis ofÂ You See Big Girlis due to its majestic cinematic music arrangement, its suitability in accompanying the battle scene, and also can be enjoyed as an independent track despite of its role in accompanying the scene. This qualitative descriptive research aimsÂ toÂ analyze the musical composition technique by describing the epic musical element. This research contains of literature study, discography, and observation as the research methods, along with the approachÂ ofÂ Lehman and Derrick WerlÃ©â€™sexamineÂ on epic music to analyze the epic element. The result shows that the You See Big Girl is one of the various epic music with the use of battle and war instrument, as well as tension built gradually from a section to the following by the use of polyrhythm, marcato accent, big crescendo, sequence, sudden silence to ends the musical phrase, ostinato, and abstract theme, to portray a majestic, vibrant, war and battle scene, and the greatness through the music.Â Keywords:Â analysis, composition, animation, epic soundtrack, You See Big GirlÂ